A novel MAC protocol for IDMA‐based multi‐beam satellite communication systems. (11th July 2013) - Ge, Xin; Liu, Gongliang; Leung, Victor C.M.; Zhang, Naitong
SUMMARY Considering the limitations of satellite communication systems and advantages of new emerging interleave‐division multiple access (IDMA) technology, IDMA is introduced into the satellite systems, providing a new solution for multiple access techniques of satellite systems. To further validate the IDMA into satellite systems, a novel medium access control (MAC) scheme is proposed. In the random access channel, the interleave‐division slotted ALOHA method is adopted to alleviate the collision of access requests. Furthermore, a novel minimum power allocation scheme based on signal‐to‐interference‐plus‐noise ratio (SINR) evolution is proposed to maximize the capacity of such an interference‐sensitive system. By virtue of SINR evolution, our proposed scheme can accurately estimate multi‐user detection efficiency with low computational cost and further reduce the transmitted power, illustrating the high power efficiency of IDMA. To further enhance the performance of the MAC protocol, an effective call admission control scheme considering the effect of power control error is designed and combined into our MAC protocol. Analysis and simulation results show that, by taking full advantage of the chip‐by‐chip multi‐user detection technique, the proposed IDMA MAC protocol achieves high throughput and low average packet delay simultaneously, with low onboard processing complexity in the multi‐beam satellite communication systems. Copyright © 2013 John Wiley & Sons, Ltd.